2014
DOI: 10.1001/jamadermatol.2013.4741
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Sunscreen Recommendation Among US Physicians

Abstract: Despite encouragement to provide patient education regarding sunscreen use and sun-protective behaviors, the rate at which physicians are mentioning sunscreen at patient visits is quite low, even for patients with a history of skin cancer. The high incidence and morbidity of skin cancer can be greatly reduced with the implementation of sun-protective behaviors, which patients should be counseled about at outpatient visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The National Ambulatory Medical Care Survey reported that ''there were an estimated 18.30 billion patient visits from January 1, 1989 to December 26, 2010'' (Akamine, Gustafson, Davis, Levender, & Feldman, 2014, p. 52). However, it is worrisome to note that less than 1% of these visits included mention of the use of sun protection, even among patients with a previous history of skin cancer (Akamine et al, 2014). Thus, educating nurse practitioners (NPs) to confidently discuss sun protection as a part of routinely recommended safety and control guidelines is necessary (Dadlani & Orlow, 2008).…”
Section: Contact Hoursmentioning
confidence: 99%
“…The National Ambulatory Medical Care Survey reported that ''there were an estimated 18.30 billion patient visits from January 1, 1989 to December 26, 2010'' (Akamine, Gustafson, Davis, Levender, & Feldman, 2014, p. 52). However, it is worrisome to note that less than 1% of these visits included mention of the use of sun protection, even among patients with a previous history of skin cancer (Akamine et al, 2014). Thus, educating nurse practitioners (NPs) to confidently discuss sun protection as a part of routinely recommended safety and control guidelines is necessary (Dadlani & Orlow, 2008).…”
Section: Contact Hoursmentioning
confidence: 99%
“…20,21 The lack of effect of counseling may contribute to 0.01% of pediatrician visits, including sun protection counseling. 22 Promisingly, other randomized controlled clinical trials with distribution of sun protection products (eg, sunscreen and clothing) increased parental knowledge and practice of sun protection behaviors. 23-25 However, none of these studies evaluated whether children receiving the intervention experienced less pigment change.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet (UV) radiation accounts for up to 90% of these cancers and is the only known modifiable risk factor associated with skin cancers [108][109][110]. While the importance of sun-protection is well recognized, excessive sunbathing and the overuse of tanning beds remains in our society.…”
Section: Tanning As An Addictionmentioning
confidence: 99%